Does exercise have a neuroprotective function in multiple sclerosis? A brief overview of the physical training potential effects on cytokines and brain-derived neurotrophic factor - David Barbado Murillo; Ramón Gómez-Illán; Pedro Moreno; Nuria Mendoza; Raul Reina Vaillo; Angel P. Sempere (Asociación Española de Ciencias del Deporte, 2018)
Although the advance in disease-modifying drugs has helped to stabilize the multiple sclerosis (MS) course increasing life-expectancy, physical deterioration still supervenes over time in most MS patients. In this context, physical exercise programs are considered a safe and well-tolerated tool to preserve functional independence in this population, which not only provides similar fitness improvements as usually observed in healthy general population, but it may also ameliorate some of the symptoms that this pathology entails (as fatigue, balance deficits, muscle weakness, etc.). Nowadays, the question is if exercise only aids to reverse physical deconditioning associated to the disease or it has the potential to have an impact on MS progression. In the present overview, the role of exercise as complementary therapy for modulating various physiopathological pathways related to MS disease such as inflammation and the neurotrophic support for neuronal survival was revised. Specifically, the exercise ability to modulate the immune system behaviour regulating the pro- and anti-inflammatory cytokine balance, as well as, to promote neuroprotective and neurorestorative mechanisms through the brain-derived neurotrophic factor stimulation was analysed.